2021
DOI: 10.1152/ajprenal.00205.2021
|View full text |Cite
|
Sign up to set email alerts
|

Specialized proresolution mediators in the bladder: annexin-A1 normalizes inflammation and bladder dysfunction during bladder outlet obstruction

Abstract: Bladder Outlet Obstruction (BOO) is ultimately experienced by ≈90% of men, most commonly secondary to benign prostatic hyperplasia. Inflammation is a critical driver of BOO pathology in the bladder and can be divided into two critical steps; initiation and resolution. While great strides have been made toward understanding initiation of inflammation in the bladder (through the NLRP3 inflammasome), no studies have examined resolution. Resolution is controlled by 5 classes of compounds known as Specialized Pro-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 63 publications
2
6
0
Order By: Relevance
“…32 Recently, we expounded on a possible role for Annexin-A1 in treating BOO using a rat model. 33 In those studies, we demonstrated the presence of all six SPM receptors in the rat bladder. Expression was predominantly urothelial with some expression in the detrusor and some changes in expression pattern in response to BOO.…”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…32 Recently, we expounded on a possible role for Annexin-A1 in treating BOO using a rat model. 33 In those studies, we demonstrated the presence of all six SPM receptors in the rat bladder. Expression was predominantly urothelial with some expression in the detrusor and some changes in expression pattern in response to BOO.…”
Section: Introductionmentioning
confidence: 61%
“…We began these studies by examining the repertoire of SPM receptors expressed in the mouse and human bladder. While our previous work documented expression in rat bladder 33 expression needed to be confirmed in these species. Our results show expression of all known SPM receptors in the bladder in both species (six in mice, seven in humans).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations